ASSESSMENT OF MAJOR RISK FACTORS OF DIABETES MELLITUS AMONG DOCTORS IN URBAN AREA AT NORTH WEST RAJASTHAN - LUNIA, GAUTAM; SETHIA, RENU (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: To determine the prevalence of diabetes mellitus and its association with risk factors among the study population. Methods: This was a cross-sectional study including 297 doctors with the minimum qualification of MBBS/BDS, working in government health care facilities in urban Bikaner from December 2019 to May 2020 at the Department of Medicine, S.P. Medical College, Bikaner, Rajasthan. Results: The mean age of the study population was 42.58±9.21 years. We found that 10.78% were current smokers, 9.18% consumed ≥6 drinks/ occasion, 66% consumed <5 fruit servings/day, 75% consumed >5 g of salt/day, 49.84% were physically inactive, 46.47% were overweight and 6.73% were obese, 14.14% had a systolic BP ≥140 mmHg, and the prevalence of diabetes mellitus was 15.82%. Diabetes mellitus was associated with age group, gender, alcohol use, overweight and obesity, raised blood pressure, and raised total cholesterol (p<0.05). Conclusion: The prevalence of risk factors for lifestyle diseases was high among health professionals. In this study, a higher prevalence of diabetes mellitus was observed than the WHO estimated prevalence of DM for India. Modifiable associated risk factors were current tobacco use, current alcohol use, raised blood pressure, and raised total cholesterol.